SUBMICROSCOPIC CHANGES OF THE RESPIRATORY ALVEOLAR MACROPHAGES AT THE LATE PERIOD AFTER EXPERIMENTAL THERMAL INJURY AND IN COMBINED USE OF LYOPHILIZED XENOGRAFT SUBSTRATE AND SURFACTANT - Nebesna, Z.M.; Volkov, K.S.; Bodnar, P.Ya.; Shuturma, O.Ya.; Kramar, S.B. (World of Medicine and Biology, 2018)
Experimental studies of the mature male rats’ lungs have been carried out at the late period following the simulated thermal injury in conditions of early necrectomy and application of minced substrate of the lyophilized xenograft and simultaneous administration of exogenous surfactant. Significant changes in the ultrastructure of the majority of macrophages, expressed by the reduced number of microvilli, pyknotic nuclei, destructed organelles in their cytoplasm and accumulation of secondary lysosomes were noted after the burn injury. It has been found that the combined use of the above agents on the 14 and 21 day of the experiment reduced the degree of destructive changes and the established normalization of the alveolar macrophages of the alveolar macrophages of the pulmonary alveoli greatly improved their morphofunctional state; young and phagocytising cells prevailed in their population composition.
Keywords: pulmonary alveolar macrophages; ultrastructural changes; thermal injury; lyophilized xenograft substrate; surfactant